Nigeria zero hunger forum - Ebonyi State - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
Zero Hunger is the No 1 goal of the 17 Sustainable Development Goals (SDGS) of UNDP. And the goal is set to do one thing. By 2030, no one will go hungry anywhere in the world.